2019
DOI: 10.3390/ijms20143456
|View full text |Cite
|
Sign up to set email alerts
|

Human Skeletal Muscle Cells Derived from the Orbicularis Oculi Have Regenerative Capacity for Duchenne Muscular Dystrophy

Abstract: Skeletal muscle stem cells (MuSCs) have been proposed as suitable candidates for cell therapy in muscular disorders since they exhibit good capacity for myogenic regeneration. However, for better therapeutic outcomes, it is necessary to isolate human MuSCs from a suitable tissue source with high myogenic differentiation. In this context, we isolated CD56+CD82+ cells from the extra eyelid tissue of young and aged patients, and tested in vitro myogenic differentiation potential. In the current study, myogenic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…To investigate the effects of microgravity on skeletal muscle atrophy, we utilized a 3D-clinorotation system to simulate microgravity conditions with human primary skeletal muscle hOM2 cells, which are derived from the orbicularis oculi ( Yamanaka et al, 2019 ). We observed that the proliferation of both myogenic cells and human iPS cells decreased in microgravity using the clinorotation ( Supplementary file 1 ), and it has been reported that initial myogenic differentiation to form myotubes is suppressed by fluid motion when the clinorotation is used ( Mansour et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effects of microgravity on skeletal muscle atrophy, we utilized a 3D-clinorotation system to simulate microgravity conditions with human primary skeletal muscle hOM2 cells, which are derived from the orbicularis oculi ( Yamanaka et al, 2019 ). We observed that the proliferation of both myogenic cells and human iPS cells decreased in microgravity using the clinorotation ( Supplementary file 1 ), and it has been reported that initial myogenic differentiation to form myotubes is suppressed by fluid motion when the clinorotation is used ( Mansour et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effects of microgravity on skeletal muscle atrophy, we utilized a 3Dclinorotation system to simulate microgravity conditions with human primary skeletal muscle hOM2 cells, which are derived from the orbicularis oculi (Yamanaka et al, 2019). We observed that the proliferation of both myogenic cells and human iPS cells decreased in microgravity (Supplementary file 1).…”
Section: Human Primary Myotubes Exhibit An Atrophic Phenotype In a Mi...mentioning
confidence: 99%
“…Clinical investigations conducted to date have attempted to treat a variety of conditions including muscular dystrophy, cardiac heart failure, and incontinence. 1 6 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical investigations conducted to date have attempted to treat a variety of conditions including muscular dystrophy, cardiac heart failure, and incontinence. [1][2][3][4][5][6] Faecal incontinence (FI) is a condition that would particularly benefit from cell-based regenerative medicine to restore functional muscle. FI affects a large portion of the general population, with an estimated prevalence of (2%-15%).…”
Section: Introductionmentioning
confidence: 99%
“…OOMs, which are rich in vascular distribution, may have regenerative capacity and play vital roles in tissue grafting and facial burn injury repair [ 4 ]. Recent reports have shown the efficacy of the ocular muscle tissue as a rich source of stem cells with high proliferation, differentiation, and therapeutic capacities [ 5 , 6 , 7 , 8 , 9 ]. In this regard, OOM-derived stem cells (OOM-SCs) have garnered much attention and application recently for disease therapy and tissue regeneration due to their self-renewal, proliferation, and trilineage differentiation capacities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%